Financing affordable housing in Niger State of Nigeria through commercial banks : trend, issues and future directions / Namnso Bassey Udoekanem - Namnso, Bassey Udoekanem (Research Management Institute (RMI), 2011)
This study explored the trend in interest rates on real estate loans granted by commercial banks in Nigeria. Primary data used for the study were collected from selected real estate firms in Minna, the capital of Niger State of Nigeria, which are active in the residential property market in the city. The secondary data were obtained from the Central Bank of Nigeria (CBN) and the National Bureau of Statistics (NBS). Results of data analysis revealed that variation in interest rates on real estate loans granted by commercial banks in Nigeria in the past three years was statistically significant at 0.05 level ofsignificance, an indication that interest rates on real estate loans granted by commercial banks in the country did not follow a similar trend. The paper examined the implications ofthis trend on affordable housing finance in Niger State of Nigeria and argues that more than 90 per cent of the households in Niger State could not afford real estate loans granted by commercial banks for housing development and acquisition in the area at the current interest rates. The paper concluded that greater involvement ofthe government at all levels in the provision of long-term real estate credit at affordable interest rates is necessary if housing finance to be made affordable for the low-income groups in Niger State, Nigeria.